The Value of Tolerance in the Huma Betang Philosophy and Its Relevance to Religious Moderation in Islamic-Dayak Relations - Wilson Wilson; Yane Octavia Rismawati Wainarisi; Alfonso Munte (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study aims to identify forms of religious moderation in Islamic-Dayak relations by examining: (1) the basic concept of tolerance in Islamic-Dayak relations, and (2) how these principles are practiced in everyday interreligious interactions. Using a descriptive qualitative approach, the research involved 15 participants, comprising academics, religious leaders, indigenous leaders, and Muslim community members in Palangka Raya City, Central Kalimantan. Data were collected through in-depth interviews and analyzed using Miles and Huberman’s (1994) qualitative analysis model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that tolerance in Islam is grounded in the teachings of the Qur’an, while in Dayak communities, it is rooted in the Huma Betang philosophy. In practice,Islamic–Dayak tolerance is reflected through freedom of religious choice within families, mutual respect and appreciation, and efforts to maintain interfaith friendship. The study concludes that strengthening Islamic–Dayak relations requires reaffirming the values of Huma Betang and fostering creative and innovative forms of interaction that remain consistent with each community’s religious doctrines. Penelitian ini bertujuan untuk mengidentifikasi bentuk-bentuk moderasi beragama dalam relasi Islam-Dayak dengan menelaah: (1) konsep dasar toleransi dalam hubungan Islam–Dayak, dan (2) bagaimana prinsip-prinsip tersebut dipraktikkan dalam interaksi antarumat beragama sehari-hari. Menggunakan pendekatan kualitatif deskriptif, penelitian ini melibatkan 15 partisipan yang terdiri atas akademisi, tokoh agama, tokoh adat, dan komunitas Muslim di Kota Palangka Raya, Kalimantan Tengah. Data dikumpulkan melalui wawancara mendalam dan dianalisis menggunakan model analisis data kualitatif Miles dan Huberman (1994), yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa toleransi dalam Islam berakar pada ajaran Al-Qur’an, sedangkan dalam masyarakat Dayak toleransi tersebut berlandaskan pada ilosofi Huma Betang. Dalam praktiknya, toleransi Islam–Dayak tercermin melalui kebebasan memilih agama dalam lingkup keluarga, sikap saling menghormati, saling menghargai, serta upaya menjaga persahabatan lintas keyakinan. Penelitian ini menyimpulkan bahwa penguatan hubungan Islam–Dayak memerlukan peneguhan kembali nilai-nilai Huma Betang serta pengembangan bentuk-bentuk relasi yang kreatif dan inovatif ang tetap selaras dengan doktrin keagamaan masing-masing komunitas.